Denotasi Mitos Pernikahan Semarga Pada Adat Mandailing di Wilayah Tapanuli Selatan - Septriani, Septriani; Mahrani, Silvia; Lubis, Fatma Anggraini (Literasi Bahasa dan Sastra Jurnal, 2025)
This study aims to analyze cultural values, customs, especially regarding the Denotation of the Myth of Marriage of the Same Clan in Mandailing Customs in the South Tapanuli Region. So that the wider community can better understand and comprehend the customary law of the Batak Mandailing. This research theory uses the Ethnography theory by Bronislaw Malinowski. The Ethnography approach seeks to provide an understanding that departs from an understanding of the culture of the community that is to be understood. The form of the results of the ethnographic research report is so distinctive, that the term ethnography is also used to refer to the research method to produce the report. This research method uses a qualitative method. This study collected data through interviews. The results of the study show that the Batak Mandailing Customary community has customary rules that prohibit marriage of the same clan based on the belief that marriage of the same clan can bring curses and bad luck to the family. However, over time this prohibition has begun to fade and is even ignored by some people. The myth of marriage of the same clan in the Mandailing custom in the South Tapanuli region is quite strong. Local people believe that marriage between people who have the same clan can bring bad luck, illness, and even death to their families, but this myth has not been scientifically proven. This myth is believed to be a form of respect for ancestors and maintaining good relations between families in one clan. This study also found that the myth of marriage within the same clan is still believed by some Batak Mandailing people.